2009
DOI: 10.1371/journal.pntd.0000402
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Cost-Effectiveness of Mass Treatment for Intestinal Nematode Worm Infections Using Different Treatment Thresholds

Abstract: BackgroundIt is estimated that almost a half of all of people living in developing countries today are infected with roundworms, hookworms, or whipworms or combinations of these types of intestinal nematode worms. They can all be treated using safe, effective, and inexpensive single-dose generic drugs costing as little as USD 0.03 per person treated when bought in bulk. The disease caused by intestinal nematodes is strongly related to the number of worms in the gut, and it is typical to find that worms tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Single-dose therapy with albendazole is more effective (72%) than mebendazole (15%) against hookworm. 28 In areas where annual distribution of ivermectin is ongoing, "piggybacking" an additional 27,29,30 and costs related to importation and transports to intervention areas. However, expanding coverage to new areas where piggybacking with other MDA programs could not occur would have a much higher incremental cost as the cost of drug delivery would need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Single-dose therapy with albendazole is more effective (72%) than mebendazole (15%) against hookworm. 28 In areas where annual distribution of ivermectin is ongoing, "piggybacking" an additional 27,29,30 and costs related to importation and transports to intervention areas. However, expanding coverage to new areas where piggybacking with other MDA programs could not occur would have a much higher incremental cost as the cost of drug delivery would need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Both place Guatemala as at the top of the ranking and Trinidad and Tobago at the bottom and, while there are some significant differences in where in the ranking the methodologies place the countries in between (Nicaragua, Dominican Republic and Chile for example), there seems to be broad similarities in the trend. However, the range of prevalence values in the Hall et al (2009) is much wider -ranging from (a perhaps implausibly high) 92.6% in Guatemala to 4.5% in Trinidad and Tobago. Our model predicts a more homogenous situation across the countries.…”
mentioning
confidence: 99%
“…Fig. 11a compares the national level STH prevalence predicted by this model to those presented by Hall et al (2009) (which are those originally arrived at by de Silva et al (2003) after applying to updated data the methodology originally employed by Chan et al (1994)). The figure reveals that the two methodologies result in a similar ranking by prevalence of the countries.…”
mentioning
confidence: 99%
“…Further research is needed to determine if the observed differences in mean egg count per gram of feces actually point toward physiological differences in fecundity across countries or whether the finding was just an artifact of diagnostic technique. It should also be noted that worm fecundity is dependent upon the density of wonns in an infection, with higher numbers of worms leading to lower individual rates of egg production (168,169).…”
Section: Life Cyclementioning
confidence: 99%
“…Intraspecific interactions within a host can have an impact on the virulence, fecundity, and population structure of a parasitic infection (168,169,233). Studies on intestinal nematodes have shown that an increase in parasite density leads to decreased individual fecundity, likely a result of intraspecific competition for resources (168,169).…”
Section: Within-host Dynamics Ofinfectionmentioning
confidence: 99%